Single-Use Flexible Bronchoscope in Facilitating Endobronchial Valve Treatment in Severe Emphysema - Sakaguchi T; Slebos DJ (International Journal of COPD)
Tadashi Sakaguchi,1,2 Dirk-Jan Slebos2,3 1Department of Respiratory Medicine, Matsusaka Municipal Hospital, Matsusaka, Mie, Japan; 2Department of Pulmonary Diseases, University of Groningen, University Medical Center Groningen, Groningen, the Netherlands; 3Groningen Research Institute for Asthma and COPD, University of Groningen, University Medical Center Groningen, Groningen, the NetherlandsCorrespondence: Tadashi Sakaguchi, Department of Respiratory Medicine, Matsusaka Municipal Hospital, 1550, Tonomachi, Matsusaka, Mie, 515-0073, Japan, Tel +81 598 23 1515, Email iwbd0524@yahoo.co.jpAbstract: Ensuring proper placement of one-way endobronchial valves is a vital step in achieving successful bronchoscopic lung volume reduction. The ability to navigate into sharply angled airways may be limited by the maximal flexion capability of bronchoscopes. We sometimes encounter difficult anatomical situations, causing a challenging, or sometimes even impossible placement of the EBV in the appropriate position due to steep bronchial bifurcation angles, particularly in the apical segments. A 56-year-old woman with severe emphysema was referred to our hospital after an incomplete EBV treatment due to a very sharp bronchial bifurcation angle in the right upper lobe apical segment (RB1). We were able to easily solve the problem by placing the final RB1 valve using a single-use therapeutic bronchoscope with a greater angulation range than conventional reusable bronchoscopes. The use of single-use therapeutic bronchoscopes with greater flexibility than conventional reusable therapeutic bronchoscopes may be a valuable approach for achieving successful EBV placement in anatomically challenging cases with sharp bronchial branching angles. Keywords: bronchoscopic lung volume reduction, emphysema, endobronchial valves, single-use bronchoscopy, Zephyr